2004
DOI: 10.1177/1087057104267604
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Assays on the BIND System

Abstract: Screening of biochemical interactions becomes simpler, less expensive, and more accurate when labels, such as fluorescent dyes, radioactive markers, and colorimetric reactions, are not required to quantify detected material. SRU Biosystems has developed a biosensor technology that is manufactured on continuous sheets of plastic film and incorporated into standard microplates and microarray slides to enable label-free assays to be performed with high throughput, high sensitivity, and low cost per assay. The bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
185
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(189 citation statements)
references
References 26 publications
(28 reference statements)
2
185
0
Order By: Relevance
“…Over the past decades, different types of optical resonant refractive index sensors have been proposed. Most of them are based on passive optical structures such as gold films for surface plasmon resonance [2,3], photonic crystals [4][5][6][7], microrings [8], microsphere [9] and microtoroid [10] that interact with an external light source via reflection, transmission or waveguide coupling. Such sensors generally detect the resonant wavelength shift due to the interaction between the evanescent electric field of the resonant modes and the target analyte deposited on the sensor surface.…”
Section: -Introductionmentioning
confidence: 99%
“…Over the past decades, different types of optical resonant refractive index sensors have been proposed. Most of them are based on passive optical structures such as gold films for surface plasmon resonance [2,3], photonic crystals [4][5][6][7], microrings [8], microsphere [9] and microtoroid [10] that interact with an external light source via reflection, transmission or waveguide coupling. Such sensors generally detect the resonant wavelength shift due to the interaction between the evanescent electric field of the resonant modes and the target analyte deposited on the sensor surface.…”
Section: -Introductionmentioning
confidence: 99%
“…Illinois established fabrication process of multichannel PhC sensor plate on a plastic well which is commonly used in chemical/biological experiments. Typical reflection spectrum from each PhC region [45] and the picture of the plates [44] are shown in Fig. 4.…”
Section: Sensor Application Of Gmrmentioning
confidence: 99%
“…8,9 Based upon data obtained by SPR, kinetic parameters and equilibrium constants of binding (i.e., on-rate, off-rate, and apparent dissociation constants) can be determined. 7,10,11 A recent study of carbonic anhydrase II that compared SPR with the traditional measurement of stopped-flow fluorescence showed that the kinetic parameters determined by SPR are in agreement with those determined by stopped-flow fluorescence.…”
Section: Optical Sensingmentioning
confidence: 99%
“…8,9 Target protein is immobilized onto a solid surface via covalent or noncovalent interaction. Binding of small-molecule compounds changes the refractive index of the immobilized target, which can be detected by optical sensing.…”
Section: Optical Sensingmentioning
confidence: 99%